Effects of goserelin administration before myomectomy on plasma homocysteine levels in patients with symptomatic uterine leiomyomata - Celik, H; Ayar, A; Kilic, N (Elsevier Science Inc, 2003)
[Abstract Not Available]
Keywords: Women